Arkila: A Progressive Web App Car Rental Management System for Kataguan Rides in La Trinidad, Benguet - Melbert Marafo; Jeverlyn Antonio; Brein Palay-en; Ginard Guaki; Charlie Toribio (Southeast Asian Journal of Science and Technology, 2025)
This study developed Arkila, a Progressive Web Application (PWA) for Car Rental Management, designed to address the inefficiencies of manual vehicle booking and management processes. Guided by the FeatureDriven Development (FDD) methodology, the project followed a structured approach consisting of six iterative stages: developing an overall model, building a features list, planning by feature, designing by feature, building by feature, and deploying for user acceptance. Functional and non-functional requirements were established through qualitative interviews, forming the basis for the system’s overall model, diagrams, and data structures. Subsequent stages involved defining prioritized features through a Feature Breakdown Structure and Milestone Map, followed by process flow designs and UI prototypes to guide development. The system was implemented using Next.js for the frontend and Firebase and Appwrite for backend services, ensuring a scalable, secure, and responsive architecture. Unit tests were conducted which validated that the features function as expected. Quantitative evaluation through a User Acceptance Test (UAT) yielded an overall mean score of 3.72, indicating that users were highly satisfied and fully accepted the platform’s functionality and usability. The results confirmed that Arkila successfully achieved its objectives of streamlining booking transactions, improving fleet coordination, and enhancing operational efficiency. Recommendations for further improvement include refining the booking flow, integrating GPS-based fleet tracking, expanding artificial intelligence capabilities, and enabling offline and mobile functionality to improve accessibility and adaptability.